Link between estrogen deficiency osteoporosis and susceptibility to bone metastases: A way towards precision medicine in cancer patients. (October 2018) - Salamanna, F.; Borsari, V.; Contartese, D.; Nicoli Aldini, N.; Fini, M.
Abstract: Different fields of cancer management consider bone health to be of increasing clinical importance for patients: 1) presence of bone metastases in many solid tumors, 2) use of bone-targeted treatments in the reduction of bone metastasis, 3) effects of cancer treatment on reproductive hormones, critical for normal bone remodeling maintenance. Additionally, bone microenvironment is further complicated by the decline of ovarian sex steroid production and by the related increase in inflammatory factors linked to menopause, which result in accelerated bone loss and increased risk of osteoporosis (OP). Similarly, cancers and metastasis to bone showed a close relationship with sex hormones (particularly estrogen). Thus, these findings raise a question: Could pre-existing estrogen deficiency OP promote and/or influence cancer cell homing and tumor growth in bone? Although some preclinical and clinical evidence exists, it is mandatory to understand this aspect that would be relevant in the clinical theatre, where physicians need to understand the treatments available to reduce the risk of skeletal disease in cancer patients. This descriptive systematic review summarizes preclinical and clinical studies dealing with bimodal interactions between pre-existing estrogen deficiency OP and bone metastasis development and provides evidence supporting differences in tumor growth and colonization between healthy and OP status. Few studies evaluated the impact of estrogen deficiency OP on the susceptibility to bone metastases. Therefore, implementing biological knowledge, could help researchers and clinicians to have a better comprehension of the importance of pre- and post-menopausal bone microenvironment and its clinical implications for precision medicine in cancer patients. Highlights: Bimodal interactions between pre-existing estrogen deficiency osteoporosis and bone metastasis development. Preclinical studies recognized relevant differences in tumor growth and colonization between healthy and osteoporotic status. No clinical trials provide useful information about estrogen deficiency osteoporosis on bone metastases susceptibility. Need of studies able to confirm impact of estrogen deficiency osteoporosis on bone metastases susceptibility.